PRODUKSI ALAT ORBITAL SHAKER DENGAN PENGATUR WAKTU DAN KECEPATAN PUTAR MENGGUNAKAN POTENSIOMETER BERBASIS ARDUINO UNO - Vicias, Icha Arum; Pauzi, Gurum Ahmad; Ayu, Humairoh Ratu; Suciyati, Sri Wahyu (Journal of Energy, Material, and Instrumentation Technology, 2024)
Mixing solutions is an everyday activity performed in laboratory spaces. Mixing solutions manually by shaking is less effective, as it takes a long time and requires much effort. Therefore, an orbital shaker has been created to mix solutions with a digital unidirectional movement. This device is designed using a DC motor as the driver, an L298N motor driver, an Arduino Uno as the processor, a potentiometer to adjust the speed and rotation time, a seven-segment TM1637 display to show the set values, and push buttons as start and reset buttons. Testing the orbital shaker begins by inputting PWM values on the potentiometer and then measuring the DC motor's rotation speed (rpm) using a tachometer. The calibration testing includes calibrating the rotation speed values (rpm) and time. The results of rotation speed calibration testing show an average error value of 1.09%, accuracy of 98.91%, and precision of 99.77%. In comparison, time calibration yields an average error value of 2.45%, accuracy of 97.55%, and precision of 99.99%. Subsequently, speed testing is conducted using a solution load ranging from 100 to 1000 g, with each increment of 100 g testing rotation speeds from 240 to 360 rpm. The results indicate that when a load is applied, there is a decrease in the measured rotation speed compared to the input speed. The orbital shaker can rotate within a speed range of 240 to 374 rpm and a maximum time of 90 minutes with a maximum load of 1000 g.